A new political lexicon in Pakistan's civil–military relations (2013–2018). Issue 2 (21st April 2022) - Ahmed, Raja Qaiser; Fatima, Rida; Shoaib, Muhammad
Abstract: The rise of a new political lexicon—indirectly referring to the military's interference in political affairs—in Pakistan's civil–military relations (2013–2018) is a recent development. It marked the beginning of a transitionary phase in the country's political culture and provided an alternative medium for political dissent. It helped strike a balance between outright confrontation and complete conformism by civilian forces in the political spectrum. The consequent formation was tactical deference on the part of civilian authorities to voice dissent. This mode of dissent became prevalent in the statements of the party leaders. It is a pioneering step toward a more inclusive and open society in the country. This study explores how did the new political lexicon impact the state and society in Pakistan. This article covers a five‐year period from 2013 to 2018.